The association between high hygiene scores and allergic rhinitis in Korean adolescents. Issue 8 (1st June 2020) - Wee, Jee Hye; Park, Min Woo; Min, Chanyang; Park, Il‐Seok; Park, Bumjung; Choi, Hyo Geun
Abstract : Background: Recent studies have proposed that handwashing can lead to the development of allergic disease by reducing skin epithelial barrier integrity. The purpose of this study was to evaluate the association between personal hygiene practices and allergic rhinitis (AR) in a nationally representative sample of Korean adolescents. Methods: A total of 62, 276 adolescent participants (aged 12 to 18 years) were analyzed using the Korea Youth Risk Behavior Web‐based Survey, which was conducted in 2017. Participants were asked about the frequency of handwashing considering 5 situations. AR histories throughout life and in the last 12 months were obtained. The associations between AR and hygiene scores were analyzed using multiple logistic regression, with adjustment for possible confounders. Subgroup analyses were conducted for school level, age, economic level, and education level of each parent. Results: The analysis of the general characteristics showed that younger age, increased number of days of physical activity, male sex, living in a large city, high economic level, high education levels of father and mother, nonsmoking status, and no alcohol consumption were associated with a relatively high hygiene score ( p < 0.001). The adjusted odds ratio (aOR) of AR was 1.12 (95% confidence interval [CI], 1.06 to 1.18; p < 0.001) throughout life and 1.21 (95% CI, 1.14 to 1.29; p < 0.001) for the previous 12 months in the highest compared with the lowest hygiene score groups. Consistent results were obtained in the female sex, any school level, middle economic level, and both parents with any education level. Conclusion: The association between high hygiene scores and AR was significant in Korean adolescents after adjustment for several variables.